Why Kansas Can Not Get Over the Learning Styles Myth: A Document Analysis - Alan English (The Advocate, 2020)
The term “learning styles theory” refers to a belief that students have individualized modes of learning which, once determined, will lead to improved classroom performance if material is presented in that specified mode. Despite a lack of empirical evidence, it is one of the most enduring and wide-spread beliefs in public education, leading many researchers to refer to it as a “myth”. This study consists of a document analysis of the Kansas State Department of Education’s website, KSDE.org, to determine the degree of influence that learning styles theory has on Kansas’s educational system. It is hoped that doing so will lead to greater conversation among all stakeholders as to how learning styles theory can be removed from Kansas classrooms. While evidence of learning styles theory’s influence on Kansas educational policy was found, more research is needed to determine the degree of influence it is having on instruction within classrooms.
Keywords: Learning Styles Theory; KSDE; Kansas